Declaration of a Corruption-Free Zone In the Prosecutor’s Office from the Perspective of Legal Theory - R. Muhamad Ibnu Mazjah; Kurdi Kurdi (Magister Hukum Universitas Semarang, 2025)
This study aims to analyze the application of psychoanalytic and empiricist learning theories in human resource (HR) development and to examine the function of law in fostering compliance through the Integrity Zone at the Trenggalek District Attorney's Office. The urgency of this study lies in the importance of the integrity and professionalism of prosecution officials as a foundation for ensuring just legal certainty. This research employs a normative legal method with a statutory and conceptual approach. The findings indicate that effective HR management reflects a psychoanalytic aspect (internal mentality) influenced by empirical factors (work environment and infrastructure) as a driving force. This driving factor is then engineered through law to shape behavior. The novelty of this research is positioning the Integrity Zone not merely as an administrative program, but as an instrument of legal engineering that consciously applies learning theories to control and prevent behavioral deviations. In conclusion, administrative law, through the declaration of an Integrity Zone, serves as a strategic tool for building a culture of compliance and accountability within law enforcement institutions.